Moral Hazard and Nonmarket Institutions: Dysfunctional Crowding Out or Peer Monitoring? - Stiglitz, Joseph E.; Arnott, Richard (American Economic Review, 1991)
We examine a situation in which insurance is characterized by moral hazard. When market insurance is provided, supplementary mutual assistance between family and friends (unobservable to market insurers) will occur. When nonmarket insurers have no better information than market insurers, the mutual assistance not only crowds out market insurance but is also harmful and therefore dysfunctional Alternatively, when nonmarket insurers can observe each other's effort perfectly, mutual assistance is beneficial These results point to the potential importance of peer-monitoring mechanisms in mitigating moral hazard.